2020
DOI: 10.7759/cureus.10607
|View full text |Cite
|
Sign up to set email alerts
|

Fever of Unknown Origin in a 17-Year-Old Girl

Abstract: Fever of unknown origin (FUO) is defined as fever (>101°F) that lasts more than three weeks and for which a cause is not found within seven days of hospital evaluation. FUO has a broad list of differentials - infection, inflammatory diseases, and malignancy. A detailed history and meticulous clinical examination with thorough and stepwise investigations lead to a diagnosis in only two-thirds of cases. In this article, we present a 17-year-old adolescent girl, with no significant past medical history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…In the diagnosis of febrile illness, doctors need to conduct a thorough evaluation and examination based on the patient's symptoms, signs and possible causes to determine the final diagnosis and treatment plan. However, despite conducting a comprehensive examination, it has been found that one-thirds of patients presenting with persistent fever remain undiagnosed [7] .…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…In the diagnosis of febrile illness, doctors need to conduct a thorough evaluation and examination based on the patient's symptoms, signs and possible causes to determine the final diagnosis and treatment plan. However, despite conducting a comprehensive examination, it has been found that one-thirds of patients presenting with persistent fever remain undiagnosed [7] .…”
Section: Introduction Backgroundmentioning
confidence: 99%